Perekonomian Khalifah Harun Al-Rasyid sebagai Alternative of Solution bagi Problematika Perekonomian Indonesia - Brillyandra, Fradini; Fadhil, Muflihul; Yusra, Yusra; Herlinda, Herlinda; Alpizar, Alpizar (Pacsasarjana UIN Sultan Syarif Kasim Riau, 2023)
The purpose of writing this article is to find out about the economic policies of Caliph Harun ar-Rasyid which can be used as an alternative solution to economic problems in Indonesia. The method the author uses is library research by collecting data regarding files about the history of Harun Al-Rasyid and the economy during Harun al-Rsayid's time through searching data from the internet and print in the form of articles and books. Research result; 1. Harun ar-Rasyid's Economic Policy; a. Trade and Industry, b. Intensive management of the agricultural sector, c. Development of agricultural science, d. Increasing state income through the tax sector, e. Monetary system. 2. Caliph Harun ar-Rasyid's Economic Policy as an Alternative Solution to Indonesia's Economic Problems; a. Agricultural Sector; 1). Activate the agricultural sector and create policies that favor farmers, by eliminating various taxes imposed and also reducing the prices of agricultural needs, for example reducing the prices of fertilizers, agricultural equipment, seeds and so on. 2) Develop agricultural science. This can be done by carrying out various research and trials to increase production in quantity and quality as well as helping to open up market share for farmers' products at national and international levels. 2) Monetary policy, using gold and silver exchange tools to minimize currency price fluctuations between countries, especially developed countries.Keywords: Economy, Harun Al-Rasyid, Alternative of Solution